2011
DOI: 10.1055/s-0031-1295461
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and the Kidney

Abstract: The mineralocorticoid aldosterone is a key regulator of blood pressure, fluid and electrolyte homeostasis, and acts via the mineralocorticoid receptor (MR). In recent years, an increasing number of studies revealed deleterious effects of aldosterone via its receptor. Especially in patients with primary hyperaldosteronism (PHA) a significant higher risk of developing cardiovascular comorbidities and comortalities was reported. Also renal insufficiency is clearly increased in patients with PHA indicating a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 58 publications
(75 reference statements)
0
22
0
1
Order By: Relevance
“…In addition, the correction rates for glomerular hyperfiltration and microalbuminuria were similar among patients with PA who received MRAs or underwent adrenalectomy [4,7]. However, we experienced complications that were related to hypoaldosteronism, which can contribute to glomerular hyperfiltration and volume retention, and subsequently lead to incorrectly low serum creatinine levels and overestimated eGFR values [22,23]. Nevertheless, hypoaldosteronism treatment increases serum creatinine levels and reduces the GFR, which is associated with posttreatment hyperkalemia [20].…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the correction rates for glomerular hyperfiltration and microalbuminuria were similar among patients with PA who received MRAs or underwent adrenalectomy [4,7]. However, we experienced complications that were related to hypoaldosteronism, which can contribute to glomerular hyperfiltration and volume retention, and subsequently lead to incorrectly low serum creatinine levels and overestimated eGFR values [22,23]. Nevertheless, hypoaldosteronism treatment increases serum creatinine levels and reduces the GFR, which is associated with posttreatment hyperkalemia [20].…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, the overproduction of aldosterone alters renal sodium and potassium handling and induces inflammation, fibrosis, mesangial cell proliferation, and podocyte injury in the kidney (18). Aldosterone excess leads to vasodilation in afferent and efferent arterioles, contributing to glomerular hyperfiltration in untreated patients (19,20). Hence, hypoaldosteronism after adrenalectomy increases serum creatinine and reduces GFR, which may lead to marked decreases in salt and water delivery, as well as reduced potassium secretion in the distal region (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although aldosterone excess as in PA is known to cause additional deleterious effects on the kidney (34), there are only a few studies investigating effectiveness of PA therapy on renal function. Ribstein et al (11) reported a decrease in urinary albumin excretion after ADX in 25 PA patients who were followed up for 6 months.…”
Section: Discussionmentioning
confidence: 99%